Brains! : not just a zombie snack - McAnulty, Stacy (Godwin Books, Henry Holt and Company, 2021)
"Brains. 78% water, 100% delicious. A zombie chef who has sworn off eating brains salivates over this super powerful organ in this ... picture book. From learning about how the brain processes messages from our five senses, to learning why wrinkly human brains are so much more powerful than smooth mouse brains, this is an introduction to the organ that does it all"--